Novel Therapeutic Mechanism of Adipose-Derived Mesenchymal Stem Cells in Osteoarthritis via Upregulation of BTG2. (15th October 2022) - Yang, Qinyan; Jin, Li; Ding, Qian; Hu, Wei; Zou, HaiBo; Xiao, Mingming; Chen, Keyuan; Yu, Yue; Shang, Jin; Huang, Xiaolun; Zhu, Yizhun
Abstract : Background. Osteoarthritis (OA) is a debilitating and degenerative joint disease, which is characterized by progressive destruction of articular cartilage. Mesenchymal stem cells (MSCs) have been implicated in the treatment of OA. However, the function of adipose-derived MSCs (AD-MSCs) in OA and its underlying mechanism remain obscure. Aim. We aimed to explore the function of AD-MSCs in OA and investigate its potential regulatory mechanism. Methods. A guinea pig model of OA was constructed. AD-MSCs injected into the articular cavity of OA guinea pigs were viewed by in vivo bioluminescence imaging. The effect of AD-MSCs on the gonarthritis of OA guinea pigs was evaluated through both macroscopic and microscopic detections. The detailed molecular mechanism was predicted by GEO databases and bioinformatics tools and then verified via mechanism experiments, including ChIP assay, DNA pulldown assay, and luciferase reporter assay. Results. AD-MSCs had a significant positive therapeutic effect on the gonarthritis of the OA model, and the overall effects of it was better than that of sodium hyaluronate (SH). B-cell translocation gene 2 (BTG2) was significantly downregulated in the articular cartilage of the OA guinea pigs. Furthermore, BTG2 was positively regulated by Krüppel-like factor 4 (KLF4) in AD-MSCs at the transcriptional level. AD-MSCs performed an effect on KLF4 expression at the transcriptional levels. Conclusion. AD-MSCs suppresses OA progression through KLF4-induced transcriptional activation of BTG2. Our findings revealed an AD-MSCs-dominated therapeutic method for OA.